Self Directed Learning of Toefl: a Narrative Inquiry - Khairatunnisa (Universitas Ahmad Dahlan, 2022)
Khairatunnisa, 2022. TOEFL Self-Directed Learning: Challenges and Solution. Thesis supervised by: 1) Drs. Akmal, M.Hum, M.Sc., Ph.D.; 2) Badli Esham Ahmad, Ph. D. Yogyakarta: Universitas Ahmad Dahlan collaboration with Universiti Teknologi MARA, Malaysia